Starting & building a nonprofit : a practical guide - Pakroo, Peri (Nolo, 2024)
"This essential guide to starting and running a nonprofit organization includes practical advice, legal information, tips, and step-by-step instructions. It explains how to develop a strategic plan and budget; recruit and manage board members, volunteers, and staff; market an organization to a target audience; raise money-including traditional methods and crowdfunding; build a website and use social media strategically; and adopt policies that are legally sound. Includes helpful checklists and a sample annual budget"--